Persistent organic pollutants in fish: biomonitoring and cocktail effect with implications for food safety. Issue 4 (3rd April 2019) - Panseri, Sara; Chiesa, Luca; Ghisleni, Gabriele; Marano, Giuseppe; Boracchi, Patrizia; Ranghieri, Valerio; Malandra, Renato M.; Roccabianca, Paola; Tecilla, Marco
ABSTRACT: The impact of anthropogenic wastes of persistent organic pollutants (POPs) on the marine environment has increased in the last decades. POPs include polychlorinated biphenyls (PCBs) and organochlorine pesticides (OCs). To assess the levels of these POPs in the wild fish population, pelagic and benthopelagic predator fish species were selected as biomonitors. For detection and quantification of POPs in muscular tissues, a simple extraction through Accelerated-Solvent-Extraction (ASE) with an 'in-line' clean up purification approach was applied, followed by a GC–MS/MS analysis. Concentrations of sum DDT, sum HCH and endrin correlated with all PCB concentrations. Significant differences among fish species were found for all OCs and all PCBs except PCB 31 and 101. Blackspot seabream had the highest PCB concentrations; OCs were highest in tuna. Due to major concerns regarding fish population losses and the possible human chronic exposure to contaminated fish, studies addressing combined effects of multiple POPs ('cocktail effect') should be implemented. Our data motivate further experimental and observational studies in fish to define adequate baseline levels for cumulative human exposure and potential role of these contaminants for food safety.